Complex Deformation at Shallow Depth During the 30 October 2016 Mw6.5 Norcia Earthquake: Interference Between Tectonic and Gravity Processes?. Issue 2 (23rd February 2020) - Delorme, A.; Grandin, R.; Klinger, Y.; Pierrot‐Deseilligny, M.; Feuillet, N.; Jacques, E.; Rupnik, E.; Morishita, Y.
Abstract: The relation between slip at the near surface and at depth during earthquakes is still not fully resolved at the moment. This deficiency leads to large uncertainties in the evaluation of the magnitude of past earthquakes based on surface observations, which is the only accessible evidence for such events. A better knowledge of the way slip distributes over distinct rupture strands within the first few kilometers from the surface would contribute greatly to reduce these uncertainties. The 30 October 2016 M w 6.5 Norcia earthquake has been captured by a variety of geodetic techniques, which provide access to the slip distribution both at depth and at the ground surface, with an unprecedented level of detail for a normal‐faulting earthquake. We first present coseismic surface offset measurements from correlation of optical satellite images of submetric resolution, which are compared to field observations made shortly after the earthquake. Based on a joint inversion of optical data together with InSAR and GPS data, we then propose a rupture model that explains the observations both at far‐field and near‐field scales. Finally, we explore different rupture geometries at shallow depth, in an attempt to better explain the near‐field deformation (i.e., within the first hundreds of meters around the fault) observed at the surface. Despite the fact that the solution is not unique, several lines of evidence suggest that gravity processes could be locally involved, which interfere with the dominant tectonic processes. Key Points: Correlation of optical images covering the Norcia earthquake allows inference of the slip distribution at depth and at the surface Decrease of slip toward the surface inferred from elastic modeling of interferograms contradicts high slip values measured at the surface Gravity processes, which interfere with dominant tectonic processes, could be locally involved and explain slip excess at the surface